2017
DOI: 10.1111/cdev.12831
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Mobile Phones on Children's and Adolescents’ Health: A Commentary

Abstract: The use of digital technology has grown rapidly during the last couple of decades. During use, mobile phones and cordless phones emit radiofrequency (RF) radiation. No previous generation has been exposed during childhood and adolescence to this kind of radiation. The brain is the main target organ for RF emissions from the handheld wireless phone. An evaluation of the scientific evidence on the brain tumor risk was made in May 2011 by the International Agency for Research on Cancer at World Health Organizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
27
0
13

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 12 publications
0
27
0
13
Order By: Relevance
“…In Sweden, 93% of adolescents have a mobile phone [4], while in the United States and China, this rate is approximately 73% and 82%, respectively [5,6]. Some previous literature emphasized the health problems related to mobile phone use and abuse among these groups, such as poor sleep quality [7], sedentary lifestyle [8], and increased risk of mental health issues [4,9]. However, the popularity of the mobile phone provides opportunities to engage youth and adolescents in innovative mobile health (mHealth) interventions that facilitate personal health care and self-management [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…In Sweden, 93% of adolescents have a mobile phone [4], while in the United States and China, this rate is approximately 73% and 82%, respectively [5,6]. Some previous literature emphasized the health problems related to mobile phone use and abuse among these groups, such as poor sleep quality [7], sedentary lifestyle [8], and increased risk of mental health issues [4,9]. However, the popularity of the mobile phone provides opportunities to engage youth and adolescents in innovative mobile health (mHealth) interventions that facilitate personal health care and self-management [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…As mentioned above adolescents might be more sensitive to light than adults, and more time using a device has been associated with a larger reduction in the melatonin response (Figueiro and Overington, 2016[120]). A systematic review of the literature uncovered 67 studies from 1999 to 2014 exploring sleep among school-aged children and adolescents, in which 90% of the studies found adverse associations between screen time and sleep outcomes such as delayed timing and shortened duration (Hale and Guan, 2015 [127]). It is important to note again here that association, or correlation, does not infer causation.…”
Section: Sleepmentioning
confidence: 99%
“…It is important to note again here that association, or correlation, does not infer causation. Furthermore, there tend to be issues with measurement error regarding screen time exposure and sleep times (Hale and Guan, 2015 [127]). For example, teens are likely to over-report sleep time, and there is little research to validate assessments of youth engagement in screen time using self-report and parent-reported measures (Hale and Guan, 2015 [128]).…”
Section: Sleepmentioning
confidence: 99%
“…También puede ser usada cuando "hay inadecuada evidencia de carcinogenicidad en humanos pero hay suficiente evidencia de carcinogenicidad en animales de experimentación"(12). Este informe ha suscitado preocupaciones sobre los posibles riesgos para la salud asociados con los campos electromagnéticos, evidenciado últimamente en las numerosas publicaciones que evalúan el nivel de exposición de los seres humanos a los mismos (13)(14)(15)(16)(17)(18).…”
Section: Introduccionunclassified